All‐Around Universal and Photoelastic Self‐Healing Elastomer with High Toughness and Resilience (Adv. Sci. 24/2021). Issue 24 (22nd December 2021) - Tolvanen, Jarkko; Nelo, Mikko; Hannu, Jari; Juuti, Jari; Jantunen, Heli
Abstract : Self‐Healing Elastomers Soft electronics seek all‐around high mechanical performance universal self‐healing elastomers. In article number 2103235, Jarkko Tolvanen and co‐workers report design strategy to achieve tough and resilient universal self‐healing elastomer. The resilin‐inspired bimodal siloxane‐based elastomer benefits from combination of soft and hard phases. The cover displays existing phase‐separated morphology during shape recovery captured by optical microscopy.